Freshwater fishes of Israel; a revised and updated annotated checklist—2023 - Çiçek, Erdoğan; Fricke, Ronald; Sungur, Sevil; Çapar, Osman Bahadir; Golani, Daniel (Zootaxa, 2023)
The current status of the freshwater fishes of Israel is revised, and an updated checklist is presented. The confirmed freshwater fishes of Israel comprise 55 species belonging to nine orders, 14 families, and 39 genera. Among these, 19 species (34.6%) are alien, and four species (7.3%) are considered endemic to Israel. The orders with the largest numbers of species in the ichthyofauna of Israel are Cypriniformes (19 species), followed by Cichliformes (14 species), Cyprinodontiformes (seven species), Mugiliformes (six species), Siluriformes (four species), Salmoniformes (two species), and the others represent one species in each. At the family level, the Cichlidae have the greatest number of species (14 species; 25.5% of the total species), followed by Cyprinidae (10 species), Leuciscidae and Mugilidae (six species in each), Aphaniidae (four species), Nemacheilidae and Poecilidae (three species in each). According to IUCN Red List criteria, among 36 naturally distributed species (alien species not included), two species are extinct (EX) and nine species (25.0%) are categorized as threatened extinctions, with two (5.6%) CR, four (11.1%) EN, and three (8.3%) VU.